Assessing Russia’s Ban on U.S. Adoptions from a Constructivist Framework of Image Construction - Alina Clay (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2016)
This paper explores Russian image construction by analyzing Russia’s Federal Law No.272-FZ, known in the U.S. and referred to in this paper as the Dima Yakovlev Law, which bans the U.S. adoption of Russian orphans. This research challenges the commonly held view that this law was solely an act of political retaliation against the U.S. by instead indicating that the law more broadly illustrates the Russian state’s long-term image construction process. The Dima Yakovlev Law presents a useful case study in this regard as it received considerable public attention from Americans and—notably so—Russians. The structure of the paper is as follows. First, the events preceding the passage of the Dima Yakovlev Law are discussed. The next sections unpack the Russian image construction process by exploring the development and lasting significance of the Soviet “happy childhood” and anti-West sentiments. The discussion then focuses on the fluidity of Russia’s national identity and mythmaking, two phenomena that have strong linkages to the image construction process. The final section provides concluding remarks regarding the lasting impact and future implications of the Dima Yakovlev Law.